1980
DOI: 10.1002/1097-0142(19801101)46:9<1945::aid-cncr2820460908>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative irradiation in carcinoma of the pancreas

Abstract: Seventeen patients with carcinoma confined to the pancreas and the peripancreatic area received preoperative radiation therapy in an attempt to increase the resectability rate and to reduce the incidence of recurrence. The tumors were considered either unresectable or of borderline resectability. The radiation dose ranged between 4000--5000 rads, the majority of patients (75%) receiving 4400--4600 rads in 4 1/2--5 weeks. After a period averaging six weeks the patients were reevaluated for surgery. Eleven patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
1

Year Published

1991
1991
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(51 citation statements)
references
References 11 publications
2
48
0
1
Order By: Relevance
“…Pilepich and Miller used preoperative radiotherapy with the result, that two of six patients who had Whipple's resection survived 5 years or longer. Clear conversion from an nonresectable to a resectable lesion could be documented in only one of six patients [59]. Ishikawa and co-workers [34] found out in a comparative case-control study, that preoperative irradiation downstages the tumour and decreases local recurrence rates and early death from local recurrence.…”
Section: Neoadjuvant Treatmentmentioning
confidence: 96%
“…Pilepich and Miller used preoperative radiotherapy with the result, that two of six patients who had Whipple's resection survived 5 years or longer. Clear conversion from an nonresectable to a resectable lesion could be documented in only one of six patients [59]. Ishikawa and co-workers [34] found out in a comparative case-control study, that preoperative irradiation downstages the tumour and decreases local recurrence rates and early death from local recurrence.…”
Section: Neoadjuvant Treatmentmentioning
confidence: 96%
“…Based on the experience of several institutions with the administration of preoperative radiotherapy for localized pancreatic cancer [7][8][9] and on the evidence suggested by the GITSG phase III trial addressing the radiopotentiating effects of chemotherapy in the adjuvant setting [10], a preoperative chemoradiation therapy pilot study was initiated at Fox Chase Cancer Center in 1986 for patients with potentially resectable stage I to stage III pancreatic cancer [1]. This protocol involved EBRT with a total dose of 5040 cGy in 28 fractions, 180 cGy/fraction, five fractions per week.…”
Section: The 5-fu Experiencementioning
confidence: 99%
“…Initial reports of preoperative radiation with or without concurrent 5-FU demonstrated that it could be administered without increased perioperative morbidity and mortality rates [42][43][44][45][46]. However, no obvious improvement in resectability or overall survival was observed.…”
Section: -Fu-based Neoadjuvant Chemoradiation Regimensmentioning
confidence: 99%